Stable SREBP-1a knockdown decreases the cell proliferation rate in human preadipocyte cells without inducing senescence - Alvarez, María Soledad (2014)
Sterol regulatory element binding proteins (SREBP), encoded by the Srebf1 and Srebf2 genes, are important regulators of genes involved in cholesterol and fatty acid metabolism. Whereas SREBP-2 controls the cholesterol synthesis, SREBP-1 proteins (-1a and -1c) function as the central hubs in lipid metabolism. Despite the key function of these transcription factors to promote adipocyte differentiation, the roles of SREBP-1 proteins during the preadipocyte state remain unknown. Here, we evaluate the role of SREBP-1 in preadipocyte proliferation using RNA interference technology. Knockdown of the SREBP-1a gene decreased the proliferation rate in human SGBS preadipocyte cell strain without inducing senescence. Furthermore, our data identified retinoblastoma binding protein 8 and cyclin-dependent kinase inhibitor 3 genes as new potential SREBP-1 targets, in addition to cyclin-dependent kinase inhibitor 1A which had already been described as a gene regulated by SREBP-1a. These data suggested a new role of SREBP-1 in adipogenesis via regulation of preadipocyte proliferation.